Trade Liberalizaiton and Oligopolistic Industries: a Welfare Appraisal - Tito Cordella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
The welfare effect of an intra-industry trade liberalization between two different countries is studied in this paper. Firms are firstly assumed to behave à la Cournot, results are then generalized in a conjectural variation model. If trade liberalization increases "world"welfare, it is nevertheless true that one country should be better off in the autarkic situation.The crucial parameters for evaluating the convenience of opening the market to foreign competition are the relative dimensions of domestic and foreign market and industry. In general small countries with oligopolistic industries have greater advantages from free trade. Consumers gains from trade liberalization are shown to be important, to open the market may , in fact, be considered a second-best competition measure if antitrust policy is not in place. Unilateral trade liberalization is studied; an example of Nash Equilibrium in policy, where only one country opens its market to foreign competition is furnished.
Keywords: 330